One-step loop-mediated isothermal amplification system for Mycobacterium marinum detection - Okumura, Kayo; Miyamoto, Yuji; Mitarai, Satoshi; Ato, Manabu (Microbiology spectrum, 2025)
Mycobacterium marinum and Mycobacterium ulcerans , which are frequently reported as etiological agents of cutaneous nontuberculous mycobacteria, exhibit similar characteristics in terms of symptomatology and patient demographics. However, there is currently no simple identification method to distinguish between these two species. The one-step loop-mediated isothermal amplification method developed in this study represents a rapid diagnostic approach that yields results in a short time frame and does not necessitate specialized precision instruments, as the results can be visually determined. Consequently, the loop-mediated isothermal amplification method established in this study is anticipated to contribute significantly to the advancement of diagnostic techniques for cutaneous nontuberculous mycobacteria.